Stimulation of Rapid Regeneration by a Magnetic Field in Paulownia Node Cultures - Rzakulieva, Aitekin; ATAK, ÇİMEN; ÇELİK, ÖZGE (My University, 2008)
In this study, the aim was to determine the effect of magnetic fields on regeneration of Paulownia node cultures. Paulownia tomentosa node cultures were used to generate explants and these explants were passed through a 2.9- 4.6-mT magnetic flux density 1 and 9 times at 2.2 and 19.8 seconds, respectively. Chlorophyll quantities, total RNA concentrations of shoots and shoot formation rates from control and treated explants were determined. While the shoot formation rate was 61.9% in the control group, this rate was increased in magnetic field experiments and shoot formation was 82.5% in the explants that were exposed to a magnetic field for a 2.2 second period. However, the regeneration percentage of the explants exposed to a MF for a period of 19.8 s was 45%. Chlorophyll a, chlorophyll b and total chlorophyll contents of the 2.2 s group were increased in comparison to the control group. Total RNA concentrations of seedlings regenerated from treatment explants treated for 2.2 seconds significantly increased in comparison to the control (p<0.05). Our experiments show that the exposure duration to MFs is an important factor for plant tissue. MFs may be used in in vitro regeneration studies rapid and for a short time.
Keywords: Paulownia tomentosa; magnetic field; in vitro regeneration; RNA; chlorophyll content